The influence of physical activity on life quality formation of elderly people - Павлова, Юлія Олександрівна (Slobozhanskyi Herald of Science and Sport, 2016)
Pavlova Iu. Purpose: to analyze the relationship between various parameters of life quality and physical activity level of older Ukrainian citizens. Material & Methods: 150 female aged 65,2±4,3 years were interviewed with MOS SF 36 and IPAQ questionnaire. Results: it is shown the values of scales Emotional role functioning (44,0 points), General Health (51,4 points) and Bodily Pain (52,2 points) can be considered as critical. Conclusions: statistically significant correlation between the numbers of metabolic equivalents used on physical activity during work (study), duration of active recreation was found